2020
DOI: 10.2478/spes-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of postural disorders among eighth grade elementary school students

Abstract: SummaryBy determining the prevalence of postural disorders among eighth grade school students it is possible to indicate the state of these disorders at the end of the elementary school level of education, and compare it to the results obtained by applying corrective treatments on high school students. Thus, the aim of the research was to determine the prevalence of postural disorders among eighth grade school children. The research was carried out on a sample of 101 eighth grade students of both genders, aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The exception is a lack of normal physiological curvature in the lumbar spine among participants attending the fifth and eighth grades, where a significant difference can be found. Analyzing the results of previous studies [27,34], a decrease in the prevalence of this postural outlier can also be noted, even though it was previously examined in a general sense for both the thoracic and lumbar spine, and not for each segment individually, as was the case in this study. These results can be associated with an increase in body muscle mass and lean body mass, as well as a greater prevalence of organized physical activity among male participants at this age [35].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The exception is a lack of normal physiological curvature in the lumbar spine among participants attending the fifth and eighth grades, where a significant difference can be found. Analyzing the results of previous studies [27,34], a decrease in the prevalence of this postural outlier can also be noted, even though it was previously examined in a general sense for both the thoracic and lumbar spine, and not for each segment individually, as was the case in this study. These results can be associated with an increase in body muscle mass and lean body mass, as well as a greater prevalence of organized physical activity among male participants at this age [35].…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, at this age, significant differences emerge in the prevalence of kypholordosis among various grades. Analyzing previous research results also revealed an increase in this postural outlier among older elementary school children [8,27,34]. These results can be explained by the increasingly greater lack of physical activity among children at this age, as well as the emergence of compensatory postural outliers, primarily resulting from primary kyphosis and scoliosis.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Among 515 subjects, 326 individuals were identified with various postural disorders in the sagittal plane, specifically including flatback, hyperkyphosis, hyperlordosis, and kypholordosis. In another study, the authors [31] also found high prevalence of postural disorders in the sagittal plane (60.4%) such as kypholordosis, flatback, hyperkyphosis, and hyperlordosis when working with eighth graders. Similar results were obtained in studies conducted in other countries.…”
Section: Discussionmentioning
confidence: 84%